2013
DOI: 10.1159/000348546
|View full text |Cite
|
Sign up to set email alerts
|

Positive Expiratory Pressure via Mask Does Not Improve Ventilation Inhomogeneity More than Huffing and Coughing in Individuals with Stable Chronic Obstructive Pulmonary Disease and Chronic Sputum Expectoration

Abstract: Background: Positive expiratory pressure (PEP) has been used to promote airway clearance in individuals with chronic obstructive pulmonary disease (COPD) for many years; however, its mechanism of action and benefits are unclear. Previous authors have suggested that PEP improves collateral ventilation via changes in lung volumes. Objectives: It was the aim of this study to determine whether PEP improves ventilation inhomogeneity more than controlled huffing and coughing in individuals with stable COPD. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…These are all very well suited to the pathophysiological dysfunction that occurs in the lungs of people with COPD, however confirmatory evidence of these mechanisms occurring in this patient group has been somewhat elusive. 21,22 A previous systematic review of PEP therapy for patients with COPD showed inconsistent findings across a limited number of small studies and highlighted a need for further research to determine any likely clinical benefits. 23 A more recent Cochrane review reported a statistically significant pooled benefit for ACTs (compared to usual care) in reducing the need for or duration of assisted ventilation during AECOPD, with larger effects suggested for PEP-based versus non-PEP-based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These are all very well suited to the pathophysiological dysfunction that occurs in the lungs of people with COPD, however confirmatory evidence of these mechanisms occurring in this patient group has been somewhat elusive. 21,22 A previous systematic review of PEP therapy for patients with COPD showed inconsistent findings across a limited number of small studies and highlighted a need for further research to determine any likely clinical benefits. 23 A more recent Cochrane review reported a statistically significant pooled benefit for ACTs (compared to usual care) in reducing the need for or duration of assisted ventilation during AECOPD, with larger effects suggested for PEP-based versus non-PEP-based techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In the design of the present study, randomized and nonrandomized articles were analyzed, in which various types of physiotherapeutic interventions in the treatment of COPD in elderly patients were presented, from the analyzed trials, 6 studies obtained a positive outcome from the proposed analysis and 3 of the studies 14,15,18 did not obtain signi cant results.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by OSADNIK, et al 15 there are no signi cant differences between the use of Hu ng and PEP, because regardless of any bene t derived from therapy there appears to be no mediation for improvements in ventilation due to changes in lung volumes 30 .…”
Section: Total Slow Expiration With Open Lateral Decubitus Glottis (Ementioning
confidence: 99%
“…Positive expiratory pressure (PEP) therapy involves breathing with slightly active expiration against mild expiratory resistance (typically 10-20 cmH 2 O) 9 . Its application via a PEP mask represents a reliable, safe, low-cost intervention that can increase lung volumes and intrathoracic pressure 10 …”
Section: Introductionmentioning
confidence: 99%